The Role and Features of the intellectual potentialof youth in innovative development of the Republic of Belarus - E. M. Babosov; F. I. Khramtsova (Проблемы постсоветского пространства, 2017)
The article is devoted to the development of methodology for the development of intellectual poten- tial of youth as a factor of innovation development of the Republic of Belarus. Essence, features, the structure of the phenomenon of “the intellectual potential of youth” as an object of public